Synthesis, Crystal Structure, and Biological Study of PtII Complexes with 4‐Acyl‐5‐pyrazolones. Issue 7 (28th January 2014) - De Pascali, Sandra A.; Migoni, Danilo; Monari, Magda; Pettinari, Caludio; Marchetti, Fabio; Muscella, Antonella; Fanizzi, Francesco P.
Abstract: The syntheses of new Pt II complexes with 4‐acyl‐5‐pyrazolones [HQ Ph = 1‐phenyl‐3‐methyl‐4‐benzoylpyrazol‐5‐one, a ; HQ py, CF3 = 1‐(2‐pyridyl)‐3‐methyl‐trifluoroacetylpyrazol‐5‐one, b ] are reported: trans ‐[PtCl2 (DMSO)(HQ Ph )] (1a ), cis ‐[PtCl2 (DMSO)(HQ Ph )] (2a ), [PtCl(DMSO)(Q py, CF3 )] (1b ), and [PtCl2 (KQ py, CF3 )] (2b ). All complexes were characterized by multinuclear ( 1 H, 13 C, 19 F, and 195 Pt), multidimensional NMR spectroscopy and single‐crystal X‐ray diffraction analyses. The isomer trans ‐[PtCl2 (DMSO)(HQ Ph )] (1a ) crystallizes in two polymorphic forms, which correspond to two different conformers. In the trans – syn conformer (1aM ) (monoclinic, space group P 21 / c ), the H atom of the enol group [O(1)H(1)] establishes an intramolecular hydrogen bond with the ketone oxygen (O2), whereas in the trans – anti conformer (1aO ) (orthorhombic, space group Pca 21 ), the same groups are involved in an analogous intermolecular H bond. Interestingly, the cis isomer (2a ) showed in solution and at room temperature slow rotation around both the Pt–N1 and the Pt–S bonds, which restrained both the acylpyrazolone and DMSO ligand motion. Moreover, the water solubility of the complexes trans ‐ and cis ‐[PtCl2 (DMSO)(HQ Ph )] (1a and2a ) and [PtCl2 (KQ py, CF3 )] (2b ) allowed to perform in vitro biological assays on platinum‐sensitive human endometrium (HeLa) and platinum‐resistant human breast (MCF‐7) cancer cell lines. It was also possible to compare their cytotoxicity to cisplatin. Interestingly, trans isomer1a showed higher cytotoxicity on HeLa cells compared to the cis isomer2a . Abstract : The complex trans ‐[PtCl2 (DMSO)(HQ Ph )], compared to its cis isomer, showed a remarkable cytotoxic effect on HeLa cells at the highest tested doses and for longer incubation times.